2006
DOI: 10.1089/ten.2006.12.403
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of Small Intestinal Tissue Using Collagen Sponge Scaffolds Seeded with Smooth Muscle Cells

Abstract: In a previously reported attempt to regenerate small intestine with autologous tissues, collagen scaffolds were used without cell seeding or with autologous mesenchymal stem cell seeding. However the regenerated intestine lacked a smooth muscle layer. To accomplish regeneration of a smooth muscle layer, this present study used collagen scaffolds seeded with the smooth muscle cells (SMC) in a canine model. Autologous SMC were isolated from stomach wall and cultured. Two types of scaffolds were fabricated: in SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 31 publications
0
66
0
4
Order By: Relevance
“…Furthermore, intestinal organoid transplantation only generates the intestinal mucosal layer. Recently, Nakase et al 30,31 reported that transplantation of smooth muscle cells onto collagen sponge scaffolds results in generation of both an intestinal smooth muscle layer as well as enteroendocrine cells and nerve tissue in the tissue-engineered small intestinal segment. However, generation of a functional, peristaltic neuromuscular unit has still not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intestinal organoid transplantation only generates the intestinal mucosal layer. Recently, Nakase et al 30,31 reported that transplantation of smooth muscle cells onto collagen sponge scaffolds results in generation of both an intestinal smooth muscle layer as well as enteroendocrine cells and nerve tissue in the tissue-engineered small intestinal segment. However, generation of a functional, peristaltic neuromuscular unit has still not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Type I collagen is also being successfully used as a substrate on a variety of materials including corneal implants. 8 Type I collagen scaffolds have been effectively used to regenerate the small intestine in dogs, 12 and a type I collagen gel has had positive results in lumbar fusion, 11 thus making it an attractive substrate for bone-to-tendon healing.…”
Section: Figure 11mentioning
confidence: 99%
“…Hori et al used autologous mesenchymal stem cells to regenerate an intestinal muscle layer with a collagen sponge as a scaffold [19]. Nakase et al reported the use of autologous smooth muscle cells isolated from stomach wall to regenerate the smooth muscle layer [20]. It is likely that a cellular component of the small intestine is needed to initiate intestinal tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%